The indian law legacy of thurgood marshall - Knowles, F. E.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Pivot, 2014)
The book tracks the development of Justice Thurgood Marshall's rationale and reason regarding Indian law. Drawing from Marshall's career preceding his appointment to the Supreme Court, it is anticipated that Marshall's views In Indian law would be consistent with his previous role as a champion of the disenfranchised in America.
Keywords: Science; Science; Science, general